2, 2, 2-Trifluoroethanol as a solvent to control nucleophilic peptide arylation12. Issue 19 (28th April 2017) - Gimenez, Diana; Dose, Anica; Robson, Nicholas L.; Sandford, Graham; Cobb, Steven L.; Coxon, Christopher R.
Abstract : Trifluoroethanol enables selective perfluoro-heteroaromatic peptide arylation of cysteine residues. Abstract : The SN Ar arylation of peptides with perfluoroaromatics provides a route by which to install a useful chemical handle that enables both 19 F-NMR analysis and further chemical modification. However, chemo-selective arylation in peptides containing multiple nucleophilic side chains currently presents a challenge to the field. Herein, we demonstrate that employing 2, 2, 2-trifluoroethanol (TFE) as a solvent in peptide SN Ar reactions significantly improves nucleophile-selectivity when compared to N, N ′-dimethylformamide (DMF).